2015
DOI: 10.1007/s11431-015-5880-6
|View full text |Cite
|
Sign up to set email alerts
|

Coupled flood and sediment transport modelling with adaptive mesh refinement

Abstract: Coupled flood and sediment transport modelling in large-scale domains has for long been hindered by the high computational cost. Adaptive mesh refinement is one of the viable ways to solving this problem without degrading the accuracy. This goal can be accomplished through mesh adaptation, e.g., mesh coarsening and refining based on the dynamic regime of the flow and sediment transport along with bed evolution. However, previous studies in this regard have been limited to cases either without involving sedimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…In this respect, the computed bed elevations were generally in reasonable agreement with the measurements. Figure 17 shows the calculated and measured water level at four pairs of gauges in a period of 20 s. It can be found that the calculated water levels at G1 and G4 are about 40 mm lower than the measurement, which are also reported by other researchers [27,35]. One possible reason is that strong 3D characteristics of the flow at the corners of the sudden expansion of the flume width cannot be resolved by 2D depth average hydrodynamic model.…”
Section: Partial Dam-break Flow Over Mobile Bedmentioning
confidence: 60%
See 2 more Smart Citations
“…In this respect, the computed bed elevations were generally in reasonable agreement with the measurements. Figure 17 shows the calculated and measured water level at four pairs of gauges in a period of 20 s. It can be found that the calculated water levels at G1 and G4 are about 40 mm lower than the measurement, which are also reported by other researchers [27,35]. One possible reason is that strong 3D characteristics of the flow at the corners of the sudden expansion of the flume width cannot be resolved by 2D depth average hydrodynamic model.…”
Section: Partial Dam-break Flow Over Mobile Bedmentioning
confidence: 60%
“…In this section, the benchmark experiment of partial dam-break flow over mobile bed, which was also performed at UCL-Belgium [16] and has been used to test morphological models by many researchers [17,21,27,35,50], is adopted here to further verify the ability of the model to simulate bed evolution of a mobile bed caused by partial dam-break flow. As shown in Figure 13, the flume is 3.6 m wide and about 36 m long.…”
Section: Partial Dam-break Flow Over Mobile Bedmentioning
confidence: 99%
See 1 more Smart Citation
“…Technically, concern arises from the increase in computational cost, especially when the TPE‐T2‐ED‐CM model is to be applied for modeling large‐scale natural debris flows characterized by a wider particle size‐distribution. In this regard, it is advisable to employ the technique of adaptive mesh refining, which is shown to save computational time efficiently by an order of magnitude (Huang et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The mesh type was, however, limited to the structured, orthogonal curvilinear coordinate system. Huang et al [18] developed an adaptive mesh refinement model for dam-break flows over mobile-bed streams. The model was validated against experimental cases with good agreements.…”
Section: Introductionmentioning
confidence: 99%